Safety of prasterone in breast cancer survivors treated with aromatase inhibitors: the VIBRA pilot study. (3rd September 2022) - Mension, E.; Alonso, I.; Cebrecos, I.; Castrejon, N.; Tortajada, M.; Matas, I.; Gómez, S.; Ribera, L.; Anglès-Acedo, S.; Castelo-Branco, C.
Abstract: Background: Due to safety concerns on estrogen-based treatments for genitourinary syndrome of menopause (GSM) in breast cancer survivors (BCS), new options are appearing, such as androgen-based treatments, which according to proprieties would not be transformed systemically to estrogens in patients receiving aromatase inhibitors (AIs). Objective: The aim of this pilot study is to assess the security and efficacy of vaginal prasterone (dehydroepiandrostenedione [DHEA]) in BCS treated with AIs. Methods: This open, prospective, pilot study included 10 BCS treated with AIs. All participants complained of severe GSM. DHEA was administrated as a vaginal ovule. Participants were instructed to use one ovule every night during the first month, and one ovule every two nights for the entire five remaining months. The patients were requested to attend seriated visits after the beginning of the prasterone treatment to evaluate symptoms, physical improvement and serum estradiol. Results: Mean serum estradiol remained low from 3.4 pg/ml to 4.3 pg/ml ( p  = 0.9136) after 6 months of follow-up. The visual analog scale of dyspareunia improved from 8.5 to mean values after treatment of 0.4 ( p  = 0.0178). The Vaginal Health Index (VHI) scale and Female Sexual Function Index improved from 9.75 to 15.8 ( p  = 0.0277) and from an initial score of 11.2 to 20.6 ( p  = 0.0277), respectively. Vaginal pH changed from basal 8.1 to final 6.5 ( p  = 0.0330). Conclusion: Symptoms and physical examination regarding sexuality and vaginal health improved significantly, while serum estradiol remained at low levels. Prasterone seems a safe and effective option to treat GSM in BCS receiving AIs.